BASIC PERFORMANCES OF AGRICULTURE IN DANUBE REGION - Popović, Vesna; Субић, Јонел; Миjајловић, Нада (Economics of Agriculture, 2011)
The rich and diverse natural resources provide the agricultural sector a signifcant role in the structure of the economy of Danube cities and municipalities in the Republic. Agriculture has particularly important role in sustainable development of urban and environmentally sensitive areas in the region. Applied production systems and techniques may differ, depending on the nature and characteristics of resource areas, but their common features must be taking care of the preservation of soil fertility, rational use of pesticides and fertilizers, maintenance of biological diversity in agro-ecosystems and contribution to economic and social sustainability of local communities.